Type of counsel and the outcome of criminal appeals: A research note - Williams, Jimmy J. (American journal of criminal justice, 1995)
Previous studies have focused on type of counsel and case outcome at trial court, but only a few have done so at the appellate level. The purpose of this research note is to provide some insight into the influence of type of counsel on the out-come of criminal appeals. Results indicate that in criminal appeals from two Florida trial courts to an intermediate appellate court type of counsel was non-significant in predicting the court’s decision. The implications of the findings are discussed.